Penerapan Restorative justice Dalam Undang-Undang No 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana: Perspektif Regulator Dan Aparat Penegak Hukum - Mustolih, Mustolih; Rahman, Faqih Zuhdi (Universitas Cokroaminoto Yogyakarta, 2026)
Restorative justice policies in Indonesia are still scattered across several regulations. This study aims to examine the importance of restorative justice implementation regulations in resolving criminal cases in Indonesia, as well as to determine the effectiveness of restorative justice from the perspectives of regulators and law enforcement officers (APH). The research methodology is normative juridical legal research with a qualitative approach. The results of the study explain that restorative justice has represented the implementation of the fourth principle in fulfilling the ideals of legal justice that live in society, where the basis of restorative justice must be integrated with the values ​​that coexist in Indonesian society. The concept of restorative justice used in the formation of policies issued by the Supreme Court, the Prosecutor's Office, and the Police benefits from implementing the idea of ​​restorative justice as a tool in resolving legal issues in Indonesia.